REPOSISI NEGARA DALAM PASAR: ANALISIS KRITIS TERHADAP ASUMSI INTERVENSI PASAR OLEH PEMERINTAH PERSPEKTIF EKONOMI ISLAM - Khairuddin Wahid (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
Inspired by reading of ideas and efforts of many Islamic economic experts in reconstructing a newconcept of Islamic economic (known as hidden pearl) to be adjusted with the development of moderneconomy, as alternative economic system, which is expected to give sophisticating answers for thecurrent economic problems which continuously become more complex and beyond conventionaleconomic theories. As the consequence, unsynchronized terminologies appear. In fact, the terminology(intervention) is usually used more in politics, getting involved in other parties’ business. Therefore, itcreates a negative sense or interpretation.This research tries to offer a new and more proper term forsubstituting intervention with controlling. The Islamic economy, the government control over market iscomprehensive, integrated and sustainable. In social science perspective, this concept is closely similarto social disorder. In terms of market, the controlling mechanism are: (1) preventive, (2) curative, (3)repressive. Therefore, it is considered to be important to have a transparent, honest and fair legalprocesses.